ANALISIS PENGARUH PEOPLE, PHYSICAL EVIDENCE, DAN PRODUCT TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA MITRA JAYA OPTIK LAMONGAN - Ratna Handayati; Henny Mahmudah (STIE Mahardhika, 2020)
Glasses are a mandatory requirement for someone with problems with their eyes. Glasses are a tool so that someone has no difficulty in seeing their views both at close range and at a distance. This study uses quantitative methods and SPSS 24 data processing tools. Obtained a tcount for people of 3.338> ttable 1.679, tcount for physical evidence of 3.222> ttable 1.679 and tcount for product of 5.784> ttable 1.679 which means people variable (X1 ), physical evidence (X2) and product (X3) partially have a significant effect on the purchase decision (Y) of Mitra Jaya Optik Lamongan. From the F test, the results of Fcount (15,544)> Ftable (2.81) which means that the people variable (X1), physical evidence (X2) and product (X3) have a simultaneous and significant effect on purchasing decisions (Y) Mitra Jaya Optik Lamongan . While the results of multiple linear regression results Y = 1.324 + 0.365 X1 + 0.338 X2 + 0.563 X3, product (X3) has a greater influence than people (X1) and physical evidence (X2). From the above results it can be concluded that people (X1), physical evidence (X2) and product (X3) have a significant influence on purchasing decisions (Y) partially or simultaneously, and it can be seen that product (X3) is the most dominant variable influence purchasing decisions (Y).